340 Phase 1 study of AMG 160, a half-life extended BiTE® (bispecific T-cell engager) therapy targeting prostate-specific membrane antigen, in patients with metastatic castration-resistant prostate cancer. (10th December 2020) - Dorff, Tanya; Rettig, Matthew; Machiels, Jean-Pascal; Lolkema, Martijn; Autio, Karen; Greil, Richard; Rottey, Sylvie; Adra, Nabil; Salvati, Mark; Poon, Shirley; Tan, Daniel; Jurida, Gabor; et al.
Abstract : Background: Prostate-specific membrane antigen (PSMA) is a clinically validated target for metastatic castration-resistant prostate cancer (mCRPC). AMG 160 BiTE® immuno-oncology therapy redirects T cells to cancer cells by binding to PSMA on cancer cells and CD3 on T cells, leading to T-cell activation, tumor-cell killing, and T-cell expansion. As the BiTE mode of action leads to an upregulation of immune checkpoints, combining AMG 160 with a PD-1 inhibitor may lead to sustained T cell–dependent killing of tumor cells. Cytokine release syndrome (CRS) is a first-dose effect induced by BiTE molecule-mediated T-cell activation. An approach to mitigate CRS is prophylaxis with an anti-inflammatory agent. Methods: The phase 1 study (NCT03792841 ) has four parts: AMG 160 monotherapy; AMG 160 in combination with pembrolizumab; AMG 160 monotherapy with etanercept prophylaxis; and AMG 160 monotherapy administered in outpatient centers with 24-hour monitoring. Included in the study are men with histologically/cytologically confirmed mCRPC who are refractory to novel androgen receptor signaling inhibitors: abiraterone, enzalutamide, darolutamide, and/or apalutamide and have failed, refused, or are unsuitable for taxanes; and who have ongoing castration with evidence of progressive disease. Patients who received prior PSMA radionuclide therapy are eligible. Patients with CNS metastases, leptomeningeal disease, spinal cord compression, or active autoimmune disease are excluded. Primary objectives are to evaluate safety and tolerability and determine the MTD or RP2D of AMG 160 monotherapy or in combination with pembrolizumab. Secondary objectives are to characterize pharmacokinetics and preliminary antitumor activity. Evaluation of preliminary antitumor activity will be based on RECIST 1.1 with Prostate Cancer Working Group 3 modifications, PSA response, CTC response, progression-free survival (radiographic and PSA), and overall survival. PSMA PET/CT and FDG PET/CT imaging will be used for evaluation of exploratory objectives (figure 1 ). The study opened in February 2019 and is currently recruiting patients. Results: N/A Conclusions: N/A Trial Registration: NCT03792841 Ethics Approval: The study was approved by all institutional ethics boards.